THE CURRICULAR REFERENCE OF ITAMARI/BA AS A MECHANISM FOR TEACHING FOR RESEARCH IN ELEMENTARY SCHOOL - FINAL YEARS - Marinho de Araujo, Luiz Carlos (2023)
This article is the result of the Completion Work of a Specialization Course in Science Teaching in Elementary School -Final Years, held at the Federal University of Reconcavo da Bahia, by the Ciencia e 10 Program. The study was carried out with the objective of identifying, in the Reference Curriculum of a municipality in Bahia, the limits and possibilities to implement Teaching by Investigation in Elementary School - Final Years in a Municipal College, as a device to promote Scientific Literacy. Qualitative research adopted document analysis as a technique; the instrument for constituting the data was systematized by the interpretative record, using the codes: EI- Investigative Teaching and AC- Scientific Literacy. The data were analyzed using the Pragmatic Method, following the steps: Construction, [De]construction and [Re]construction of the data. It was evidenced that there is a possibility of inserting Teaching by Investigation from the Reference in the Science classes of Elementary School- Final Years.